Chronic Headaches After a Concussion in an Obese 16-Year-Old Girl. Issue 9 (November 2016) - Kumar, Maya; Gahagan, Sheila; Pickering, Bretten; Gold, Jeffrey; Stein, Martin T.
Abstract : CASE: Jennifer is a 16-year-old Latina girl who is new to your practice. During her first well visit, she mentions that she has had daily headaches for 2 years. They began after sustaining a concussion in a car accident. Typically, her headaches are bilateral and "squeezing"; they occur in the afternoons and last for a few hours. Her concussion also resulted in depressed mood, which has improved over time. When you ask if her headaches have changed recently, she says that they have been worse for the last few days. The quality and severity are unchanged; however, they now occur first thing in the morning, are worse when supine, and no longer remit. In the last 2 days, she has developed new-onset blurry vision, nausea, dizziness, photophobia, and sonophobia. Although she previously experienced sadness with her concussion, she now feels irritable. She has never used tobacco, alcohol, or drugs, and she takes no medications. On examination, her body mass index is above the 99th percentile. You note mild papilledema bilaterally. She has no focal neurological deficits. The remainder of her examination is normal. You send her to an emergency department. Her head computed tomography is normal. A lumbar puncture demonstrates an opening pressure of 32 cm H2 O; she feels relief after the procedure. She is admitted with a diagnosis of benign intracranial hypertension and is started on acetazolamide. What is the differential diagnosis of chronic headaches in an obese adolescent? How should a busy community pediatrician manage Jennifer acutely? What follow-up care should Jennifer receive?